2004
DOI: 10.1074/jbc.m404631200
|View full text |Cite
|
Sign up to set email alerts
|

Binding and Kinetic Mechanisms of the Zeta Class Glutathione Transferase

Abstract: The Zeta class of glutathione transferases (GSTs) has only recently been discovered and hence has been poorly characterized. Here we investigate the substrate binding and kinetic mechanisms of the human Zeta class GSTZ1c-1c by means of pre-steady state and steady-state experiments and site-directed mutagenesis. Binding of GSH occurs at a very low rate compared with that observed for the more recently evolved GSTs (Alpha, Mu, and Pi classes). Moreover, the single step binding mechanism observed in this enzyme i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Cys16 was found to be particularly important in maintaining proper binding and orientation with GSH. Mutation of Cys16 to Ala caused dramatic increases in K m values for GSH with various substrates (Board et al, 2003;Ricci et al, 2004). As demonstrated in mouse GSTA4, the mitochondrial form is more heavily phosphorylated than the cytosolic form while possessing the same primary protein sequence (Robin et al, 2003).…”
Section: Mitochondrion As a Site Of Dichloroacetate Biotransformation 91mentioning
confidence: 93%
“…Cys16 was found to be particularly important in maintaining proper binding and orientation with GSH. Mutation of Cys16 to Ala caused dramatic increases in K m values for GSH with various substrates (Board et al, 2003;Ricci et al, 2004). As demonstrated in mouse GSTA4, the mitochondrial form is more heavily phosphorylated than the cytosolic form while possessing the same primary protein sequence (Robin et al, 2003).…”
Section: Mitochondrion As a Site Of Dichloroacetate Biotransformation 91mentioning
confidence: 93%
“…Kinetic studies with hGSTZ1c-1c indicate that the activesite Cys16 is not a catalytic residue, although Cys16 is has an important role in binding of both GSH and electrophilic cosubstrates (Board et al 2003;Ricci et al 2004). The enzyme also shows half-site reactivity: binding of GSH to one subunit effectively silences the second subunit as it is unable to bind and activate GSH (Ricci et al 2004).…”
Section: Theta-class (Gstt)mentioning
confidence: 99%
“…Since activation parameters are the difference in energy from the activated E:S # complex and the E:S ground state, we sought to investigate the energy profile of the E:S complex formation. It has been demonstrated that GST enzymes catalysing the conjugation of GSH and CDNB are under a rapid-equilibrium random mechanism [42][43][44][45][46]. Assuming that GSTU23 is also under a rapid-equilibrium mechanism, K m can be considered as K D and a ΔG° for the E:S complex formation can be calculated [47].…”
Section: Oxidation Affects Gstu23 Kineticsmentioning
confidence: 99%